Radiocarbon dates from samples funded by English Heritage between 2006 and 2010 - Bayliss, Alexandra; Bronk Ramsey, Christopher; Cook, Gordon; Marshall, Peter; Plicht, Johannes van der (Historic England, 2023)
This volume holds a datelist of 1202 radiocarbon measurements carried out between 2006 and 2010 on behalf of the Research Department of English Heritage (including 125 undertaken in support of research funded by the Aggregates Levy Sustainability Fund (ALSF) between April 2007 and March 2010). It contains supporting information about the samples and the sites producing them, a comprehensive bibliography, and two indexes for reference and analysis. An introduction provides discussion of the character and taphonomy of the dated samples and information about the methods used for the analyses reported and their calibration. The datelist has been collated from information provided by the submitters of the samples and the dating laboratories. Many of the sites and projects from which dates have been obtained are now published, although further chronological modelling and synthesis may be undertaken on the basis of these data. The purpose of this volume is to provide easy access to the raw scientific and contextual data which may be used in further research
Keywords: Geschichte 2006-2010; Radiokarbonmethode; Großbritannien; Radiocarbon dating / Great Britain; Datation / Méthode du carbone 14 / Grande-Bretagne; Radiocarbon dating; Great Britain / https://id.oclc.org/worldcat/entity/E39PBJdmp7p3cx8hpmJ8HvmTpP